The Media, European Integration and the Rise of Euro-journalism, 1950s–1970s, Martin Herzer (2019). (1st June 2020) - Ojala, Markus
The Media, European Integration and the Rise of Euro-journalism, 1950s–1970s, Martin Herzer (2019), 1st ed.London: Palgrave Macmillan, 357 pp., ISBN 978-3-03028-777-1, h/bk, €82.49, ISBN 978-3-03028-778-8, e/bk, €64.19